2019
DOI: 10.3390/catal9030244
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Phase-Transfer Catalysts with Hydrogen Bond: A Powerful Tool in the Asymmetric Synthesis

Abstract: Asymmetric phase-transfer catalysis has been widely applied into organic synthesis for efficiently creating chiral functional molecules. In the past decades, chiral phase-transfer catalysts with proton donating groups are emerging as an extremely significant strategy in the design of novel catalysts, and a large number of enantioselective reactions have been developed. In particular, the proton donating groups including phenol, amide, and (thio)-urea exhibited unique properties for cooperating with the phase-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…Although less popular than toluene or dichloromethane in phase transfer catalysis set up, due to its pronounced acidity, chloroform has been successfully used and results obtained were comparable to those of other solvents, i.e. toluene or dichloromethane [90,91] . Hence, the conditions used in the titration experiments were similar enough to be representative of other set up carried on in different solvents.…”
Section: Resultsmentioning
confidence: 82%
“…Although less popular than toluene or dichloromethane in phase transfer catalysis set up, due to its pronounced acidity, chloroform has been successfully used and results obtained were comparable to those of other solvents, i.e. toluene or dichloromethane [90,91] . Hence, the conditions used in the titration experiments were similar enough to be representative of other set up carried on in different solvents.…”
Section: Resultsmentioning
confidence: 82%
“…The synthesis and applications of bifunctional phase-transfer catalysts are very attractive to academies and industries for their high efficiency and environmental sustainability. [25][26][27][28][29] These Bif-PTCs usually contain both one quaternary onium salt center and at least one hydrogen-bonding donor group in their structures. The hydrogen-bonding donor groups include hydroxyl (-OH), (thio)urea and squaramide.…”
Section: The Preparation Of Bifunctional Phase-transfer Catalysts (Bimentioning
confidence: 99%
“…There is a diversity of non-covalent interactions, but the introduction of strong, directional hydrogen bonds [10][11][12] in particular, are known to be crucial in the success of organocatalysed reactions It is well-known that the anion of the PTCs is usually situated proximally to the positively-charged nitrogen or phosphorous atom, establishing a strict (/tight) ion pairing interaction. 13,14 By introducing secondary interactions, as in recent studies, ion pairing has found wide application in PTC-promoted asymmetric reactions 3 ( Figure 1 left). In bifunctional PTCs, however, ion pairing processes compete with the establishment of an intermolecular hydrogen bond between the PTC counteranion and potential hydrogen bond donors.…”
mentioning
confidence: 91%